Perceived Benefits and Challenges of a Multiethnic-Racial Identity: Insight From Adults With Mixed Heritage. Issue 4 (2nd October 2017) - Soliz, Jordan; Cronan, Sierra; Bergquist, Gretchen; Nuru, Audra K.; Rittenour, Christine E.
ABSTRACT: The purpose of this inquiry was to explore the lived experiences of multiethnic-racial individuals (i.e., individuals with parents from different ethnic-racial groups). In-depth interviews were conducted with 29 adults from the United States with mixed ethnic-racial backgrounds ranging in age from 18 to 52 (female  n = 20, male n  = 9). We identified a number of themes related to perceived benefits (e.g., pluralistic world views, stronger sense of self) and challenges (e.g., identity tensions, communal concerns) of having a mixed heritage. Findings are discussed in terms of four considerations for ethnic-racial identity of individuals with mixed ethnic-racial backgrounds: emphasizing constellations of experiences, life-span and developmental considerations of identity, (mixed) ethnic-racial identity as constituted in interactions, and the potential promise of pluralistic world views.